Fabrication and dynamic compressive response of laminated ZrO–Zr2CN/Si3N4 ceramics. Issue 7 (August 2015) - Li, Liangjun; Cheng, Laifei; Fan, Shangwu; Gao, Xiaoju; Xie, YuPeng; Zhang, Litong
Abstract: Laminated ZrO–Zr2 CN/Si3 N4 ceramics with soft and hard interbedded layers and an in-situ interface were prepared via tape casting and reactive hot pressing, and the dynamic compressive response was investigated using a Split Hopkinson pressure bar tester at a range of high strain rates from 1.1×10 3  s −1 to 3.5×10 3  s −1 . With increasing the strain rates, the duration and energy of transmitted wave decreased, but that of reflected wave as well as the failure strain increased continuously. The energy absorptivity kept at a high stable level. The four characteristic stages of the stress–strain curves were inelastic loading region, stable loading region, pseudoplastic deformation region and failure region. The laminated ceramics possessed longer stable loading region but shorter pseudoplastic deformation region at higher high-strain-rates. The failure model consisting of a three-part process of multi-reflection of stress waves, crack initiation and crack deflection at the interfaces was established.